Privacy and the past : research, law, archives, ethics - Lawrence, Susan C. (Critical issues in health and medicine., 2016)
"In 2006, a HIPAA Compliance Officer in a rural Iowa county wanted to shut down a graduate student's research on a manuscript register of those admitted to a poor farm in the nineteenth century. The reason? It contained sensitive health information that could affect the well-being of living county residents. The 2003 HIPAA Privacy Rule did, in fact, protect this document from historians' prying eyes. In Privacy and the Past, Susan C. Lawrence explores why she found this experience so troubling. In the process, she explores historians' ethical obligations to their research subjects, both the living and the dead. She queries the extent to which we do and should control access to information about people as historical actors and as unwitting participants in past events. She questions who gets to decide what is revealed and what is kept hidden in decades-old records. She examines laws and court cases, and tackles archives and archivists. She looks at how demands to maintain individual privacy both protect and erase the identities of people whose stories make up the historical record. She encourages historians to vigorously resist any expansion of regulatory language that extends privacy protections to the dead. This book offers a critical analysis of the ways that broad privacy concerns shape how and when historians can understand individuals' lives as they created our collective American past."--